Improving Student Religious Behavior in Southern Thailand: The Important Role of Teachers in the Context of Islamic Education - Ramadhan, Nabil Auliya; Lisnawati, Santi (Jujurnal Publisher, 2024)
This research aims to identify, analyze, and present the crucial role of teachers in enhancing students' religious behavior at Solihuddin School, South Thailand, enriched with Islamic values perspective. The study employs a qualitative approach to explore and describe the conditions at Solihuddin School, South Thailand. Data collection involves interviews, observations, and documentary studies, with the researcher ensuring data validity through triangulation. Data analysis emphasizes steps such as data reduction, data presentation, and conclusion drawing. Findings indicate challenges in students' religious practices, including reluctance to participate in religious activities and behaviors not in line with Islamic norms. To address this, teachers at Solihuddin School, South Thailand, regularly monitor students to ensure adherence to religious practices and guide them towards behaviors aligned with Islamic values. Teachers deserve respect for their crucial role in imparting knowledge, nurturing spiritual wisdom, and leading the community spiritually. They are valued for their significant contribution to guiding individuals towards understanding and practicing religion appropriately. As influential figures in students' character development, teachers have a significant actor to instill positive moral and spiritual values during the educational process.